2020
DOI: 10.1111/ijd.15069
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological and epidemiological profile of patients with albinism in Togo in 2019: results of two consultation campaigns

Abstract: Background People with albinism (PWA) are targets of prejudice and social exclusion and have limited access to specialized medical care and resources. Our study aimed to describe the epidemiological and dermatological profile of PWA in Togo. Method We carried out a cross‐sectional study of 294 medical records of PWA systematically examined during two mobile skin care clinics in 2019. Results The mean age of the patients was 22 ± 16.5 years, and the gender ratio (M/F) was 1. A family history of albinism was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(66 reference statements)
1
2
0
4
Order By: Relevance
“…The mean age of 24.5 years in our study aligns with the mean ages reported in previous studies 3,10,11 While it is encouraging that almost 80% of the participants used sunscreen at baseline, more than 40% were applying it in the evening, when it would be less effective. By the end of the study, there was a significant improvement in understanding of the risks of sun exposure, an alignment between the knowledge acquired and the habits and attitudes toward the sun.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean age of 24.5 years in our study aligns with the mean ages reported in previous studies 3,10,11 While it is encouraging that almost 80% of the participants used sunscreen at baseline, more than 40% were applying it in the evening, when it would be less effective. By the end of the study, there was a significant improvement in understanding of the risks of sun exposure, an alignment between the knowledge acquired and the habits and attitudes toward the sun.…”
Section: Discussionsupporting
confidence: 90%
“…Many PWA develop advanced skin cancers in the third to fourth decade of life. 2,3 Measures to minimize sun damage are necessary to prevent avoidable deaths. These include: sun avoidance, wearing sun protective clothing, and regular application of sunscreens 4 as well as regular clinical review to detect and treat early skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…К факторам риска возникновения актинического кератоза и актинического хейлита относят: избыточное кумулятивное ультрафиолетовое излучение; профессиональную деятельность и профессиональные вредности; отягощенный солнечный анамнез; I и II типы фоточувствительности кожи по Фитцпатрику; актинические поражения кожи и рубцы; генетические заболевания; рентгеновское и/или инфракрасное излучение; иммуносупрессию и иммунодефицитные состояния; низкий социально-экономический статус пациента; курение [1][2][3][5][6][7][8][9][10][11][12][13].…”
unclassified
“…Известно, что у реципиентов трансплантатов первично-множественный ПКР кожи развивается в 31% случаев [2,3,5,15]. При отягощенном личном онкологическом анамнезе по раку кожи темп малигнизации очагов актинического кератоза составляет 0,53% в год [4,11]. У пациентов с генетическими синдромами плоскоклеточная карцинома развивается в более молодом возрасте.…”
unclassified
See 1 more Smart Citation